2014
DOI: 10.11648/j.ajmp.20140302.13
|View full text |Cite
|
Sign up to set email alerts
|

Optical, Morphological and Electrical Properties of Silver and Aluminium Metallization Contacts for Solar Cells

Abstract: A lower resistivity and better spectra selectivity is a measurement of the quality and potential use of silver Ag and aluminium Al metals for the application as metallization contacts for solar cells. Aluminium (Al) and silver (Ag) thin films deposited by thermal evaporation at room temperature were dense with small grain sizes, and maintained a high value of reflectance (in the spectral range from 300 to 3200 nm) with annealing at 300 °C in an argon atmosphere. Experimental results indicate that the surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Aluminium films used as metallization contacts have low specific resistivity, good thermal stability, high uniformity across the flat substrate, low particle contamination, and good adherence to substrate. These properties have led aluminium to be irreplaceable and its demand is on increase in many areas of today's rapidly developing technology especially optical industries [16]. Highly specular aluminium films made in an ultrahigh vacuum deposition process have a solar reflectance of 92%.…”
Section: Materials Processingmentioning
confidence: 99%
“…Aluminium films used as metallization contacts have low specific resistivity, good thermal stability, high uniformity across the flat substrate, low particle contamination, and good adherence to substrate. These properties have led aluminium to be irreplaceable and its demand is on increase in many areas of today's rapidly developing technology especially optical industries [16]. Highly specular aluminium films made in an ultrahigh vacuum deposition process have a solar reflectance of 92%.…”
Section: Materials Processingmentioning
confidence: 99%
“…It has been reported that the surface roughness and work function of Ag metal films are very important to increase the stability and efficiency of electrical contacts of solar cell. The optical properties of Ag metal films are decreased and their surface roughness and adhesion to substrates are increased by heat treatment in air [22]. Also the heterojunction response to light is improved and stabilised upon annealing in air [23].…”
Section: Preparation Of Thin-film Solar Cell With P-n Heterojunctionmentioning
confidence: 99%
“…The ITO has dual property in nature i.e., allow incident light to the photoactive layer in the visible spectrum range due to high work function and also collect carrier when used as an electrode [16]. On the other hand, Al has high reflectance at room temperature, low manufacturing cost, excellent thermal stability, low specific resistivity, acceptable adherence and uniformity along flat substrate [17]. Zinc oxide (ZnO) and titanium dioxide (TiO 2 ) materials, which have low resistivity, are used as window layer and electron transport layer (ETL) for better light transmission, high electron mobility and also act as hole blocking layer (HBL) to reduce the recombination losses.…”
Section: Device Modelingmentioning
confidence: 99%